ERRORS IN USING AFFIXES OF EXPOSITION TEXT AT ELEVENTH-GRADE STUDENTS OF SMA NEGERI 1 TAPUNG HULU - Sri Widowati; Charlina; Elvrin Septyanti (Jurnal PAJAR (Pendidikan dan Pengajaran), 2023)
This paper describes and analyzes the errors in the use of affixes in the exposition text for students in class X of SMA Negeri 1 Tapung Hulu. The research is qualitative research using the descriptive-analytical method, which analyzes and explains the data found in the form of words. Data analysis techniques began with data reduction, presentation, conclusion, and data verification. The data collection technique used was the writing skill test and note-taking techniques. The research data source of the exposition text was written by students. Based on the research results, five types of errors in the use of affixes were found. There were errors in the use of prefixes ber-, ter-, di-, meN-, ke-, and peN-. There was the misuse of infixes –em- and –el-. There was the misuse of suffixes -an, –i, and –kan. There were errors in the use of confixes pen-an, ber-an, ke-an, and per-an. There was incorrect use of join affixes meN-per-kan, ter-per-, di-kan, di-per-i, meN-kan, ke- to meN-per, and -i.